PsycEXTRA Dataset 2012
DOI: 10.1037/e563332012-001
|View full text |Cite
|
Sign up to set email alerts
|

Distraction Effects of In-Vehicle Tasks Requiring Number and Text Entry Using Auto Alliance's Principle 2.1B Verification Procedure

Abstract: An experiment was conducted to assess the distraction potential of secondary tasks using the Alliance of Automotive Manufacturers' Principle 2.1B verification procedure implemented using specifications obtained from an Alliance member company. Secondary tasks included radio tuning, destination entry, 10-digit dialing, dialing via contact selection, and text messaging were performed using the original equipment systems of a 2010 Toyota Prius V and an iPhone 3GS smart phone. Sixty-three participants 35 to 54 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Regarding the physiological impact, reports suggest that using a cell phone while driving delays drivers' reactions as much as having a blood alcohol level at or above the legal limit of .08% (Strayer, Drews, and Crouch 2006). Furthermore, text-messaging has been shown to be associated with the highest level of potential distraction (Dingus, Hanowski, and Klauer 2011;Ranney et al 2012). For example, studies show that drivers who retrieve or send text messages are four times more likely to be in an accident serious enough to injure themselves and/or others (Hosking, Young, and Regan 2006;Redelmeier and Tibshirani 1997).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Regarding the physiological impact, reports suggest that using a cell phone while driving delays drivers' reactions as much as having a blood alcohol level at or above the legal limit of .08% (Strayer, Drews, and Crouch 2006). Furthermore, text-messaging has been shown to be associated with the highest level of potential distraction (Dingus, Hanowski, and Klauer 2011;Ranney et al 2012). For example, studies show that drivers who retrieve or send text messages are four times more likely to be in an accident serious enough to injure themselves and/or others (Hosking, Young, and Regan 2006;Redelmeier and Tibshirani 1997).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Among all cell phone uses, Ranney et al (2012) found that texting resulted in the highest level among all sources of distraction. Hedlund (2006) reported that cell phone use was responsible for 15-25% of all RTCs.…”
Section: Distracted Drivingmentioning
confidence: 99%
“…Increased variability in the standard deviation of lane position or the standard deviation of velocity could follow from decreased attention to either of these activities. These two measures are often used by automobile manufacturers to determine the impact of secondary tasks on driving performance (14).…”
Section: Effects Of a Pc-based Attention Maintenance Training Program On Driver Behavior Can Last Up To Four Monthsmentioning
confidence: 99%